Research on Friction Stir Spot Welding Brazing Process and Properties of Dissimilar Metals DP590 and 6061 - Kai Xu; Shu-quan Zhang (Advances in Materials Science and Engineering)
Friction stir welding (FSW) is the most popular and efficient method for solid-state joining of similar or dissimilar metals and alloys. This technology is mostly applied in aerospace, rail, automotive, and marine industries. In order to reduce the weight of special auto parts, friction stir spot welding (FSSW) was proposed by some researchers for the connection of steel-aluminium dissimilar metals. However, the steel-aluminium joints welded by FSSW are prone to brittle fracture and have lower shear load although they have high mechanical connection strength. The friction stir spot welding brazing process integrates the brazing effects with the friction welding effects by the addition of solder. A study of FSSW of DP590 and 6061 with the filler metal added was carried out in this paper. The orthogonal test was performed to optimize the process parameters in order to achieve the best shear load of the joint. The shear strength of the joint was studied by the shear test. The fracture morphology was investigated by optical microscopy (OM), scanning electron microscope (SEM), and energy dispersive spectrometer (EDS). The results showed that the shear load of the joint could reach 13.239 kN when the rotating speed, depth, and residence time of the mixing head were 1000 r/min, 0.2 mm, and 90 s, respectively. The aluminium-zinc solder added could well wet the interface between aluminium and steel and promote the metallurgical bonding, thereby improving the shear load of the joint. The temperature field of DP590/6061 FSSW process was simulated by ANSYS software to verify the rationality of the optimal process parameters. The simulation results were confirmed to be basically consistent with the data measured by the thermocouple.